2017
DOI: 10.3842/sigma.2017.097
|View full text |Cite
|
Sign up to set email alerts
|

An Application of the Moving Frame Method to Integral Geometry in the Heisenberg Group

Abstract: Abstract. We show the fundamental theorems of curves and surfaces in the 3-dimensional Heisenberg group and find a complete set of invariants for curves and surfaces respectively. The proofs are based on Cartan's method of moving frames and Lie group theory. As an application of the main theorems, a Crofton-type formula is proved in terms of p-area which naturally arises from the variation of volume. The application makes a connection between CR geometry and integral geometry.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 24 publications
(32 reference statements)
0
27
0
Order By: Relevance
“…The results in [4] and [5] have been used by Ferrari and Valdinoci [16, § 2] to obtain geometric inequalities in H 1 . Several recent works use the distance function and techniques of Integral Geometry to obtain geometric inequalities in sub-Riemannian manifolds (e.g., [9], [13], [27]). From the Brunn-Minkowski type inequality obtained by Leonardi and Masnou [30], lower estimates of the volume of a tubular neighborhood of a given set can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The results in [4] and [5] have been used by Ferrari and Valdinoci [16, § 2] to obtain geometric inequalities in H 1 . Several recent works use the distance function and techniques of Integral Geometry to obtain geometric inequalities in sub-Riemannian manifolds (e.g., [9], [13], [27]). From the Brunn-Minkowski type inequality obtained by Leonardi and Masnou [30], lower estimates of the volume of a tubular neighborhood of a given set can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Along the curve γ, as in [1], we define the p-curvatures κ j (s), 1 ≤ j ≤ n and the contact normality τ (s) as We point out that all quantities above are invariant under the group actions of P SH(n). Our main theorem shows that those invariants completely determine the non-degenerate horizontally regular curve up to a Heisenberg rigid motion, which is analogues to the fundamental theorem of curves in R n .…”
Section: Introductionmentioning
confidence: 99%
“…In Proposition 4.1 in [15], the authors showed that any horizontally regular curve can be parametrized by the horizontal arc-length s such that |γ ξ (s)| = . Throughout the article, we always assume that the curve (or line) is parametrized under this condition.…”
Section: Invariants For Sets Of Horizontal Linesmentioning
confidence: 99%
“…Similarly to the group of rigid motions in R , in the previous work [15] we showed that any pseudohermitian transformation Φ Q,α ∈ PSH( ) can be represented by a left-invariant translation L Q for Q = (a, b, c) ∈ R and a rotation Rα ∈ SO( ). Actually there exists the following one-to-one correspondence between the group actions and the matrix multiplications…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation